Louis IV of France at the Council of Ingelheim in 948 (engraving) - Auteur inconnu (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Louis IV of France at the Council of Ingelheim in 948 (engraving). Louis IV of France at the Council of Ingelheim in 948 (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie